2023
DOI: 10.3390/ijerph20042857
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Physical Activity Frequency and Self-Perceived Health, Self-Reported Depression, and Depressive Symptoms in Spanish Older Adults with Diabetes: A Cross-Sectional Study

Abstract: Diabetes is one of the most prevalent noncommunicable diseases in the world. This disease can affect both physical and mental health in the population. This study analyzed the prevalence of Self-Perceived Health (SPH), self-reported depression, and depressive symptoms in comparison with the Physical Activity Frequency (PAF) reported by Spanish older adults with diabetes. A cross-sectional study was carried out with data from 2799 self-reported diabetic participants, all of whom were residents of Spain, aged 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 94 publications
0
1
0
1
Order By: Relevance
“…La obesidad puede afectar la autoestima y la imagen corporal, lo que puede llevar a la depresión. Esto es ahondado con la resistencia a la insulina y la inflamación crónica que aumentan los síntomas de la diabetes que causa aún más daño emocional (20).…”
Section: Factores De Riesgounclassified
“…La obesidad puede afectar la autoestima y la imagen corporal, lo que puede llevar a la depresión. Esto es ahondado con la resistencia a la insulina y la inflamación crónica que aumentan los síntomas de la diabetes que causa aún más daño emocional (20).…”
Section: Factores De Riesgounclassified
“…Several studies have demonstrated that physical inactivity promotes body adiposity [ 3 , 4 , 5 ]. It is well known that the accumulation of body fat, mainly in the abdomen, is strongly associated with the presence of cardiometabolic risks such as high blood pressure, insulin resistance, dyslipidemia, diabetes mellitus, and metabolic syndrome, among others [ 6 , 7 , 8 ], because visceral fat is an active metabolic tissue that modulates numerous adipocytokines associated with non-communicable chronic diseases [ 9 ].…”
Section: Introductionmentioning
confidence: 99%